Indestructible one man's rescue mission that changed the course of WWII - Bruning, John R. author (New York, NY Hachette Books, 2016)
"This little-known WWII story introduces a renegade pilot whose personal mission to rescue his family from a POW camp changed modern air warfare forever. December 1941: Manila is invaded, and US citizen and Philippine Airlines manager, Pappy Gunn, is ordered to fly key military command out of the country, leaving his family at home. So Gunn was miles away when the Japanese captured his wife and children, placing them in an internment camp where they faced disease, abuse, and starvation. Gunn spent three years trying to rescue them. His exploits became legend as he revolutionized the art of air warfare, devising his own weaponry, missions, and combat strategies. By the end of the war, Pappy's ingenuity and flair for innovation helped transform MacArthur's air force into the scourge of the Pacific"--Provided by publisher.
Part 1 Philippine odyssey -- The last normal day -- The mysterious traveler -- Into the storm -- The voice of Manila -- The day of fiestas -- Terror in the night -- Silver screen scenes -- Running toward trouble -- The middle-aged recruit -- Outlaw son of a lawman -- The noose -- American red baron -- Refugee allies -- Routine in chaos -- Christmas eve -- The last broadcast -- Part 2 The legend of Pappy Gunn -- Early legends -- The perilous consequence of not in stock -- Daniel Boone of the Dutch East Indies -- Eighth avenue rules -- Pappy and Miss EMF -- Voiding the warranty -- Where the weak are prey -- Wainwright to Macarthur: where is Captain Gunn? -- The indomitable luck of Pappy Gunn -- The Canberra commandos and the numerous troubles that ensued -- Killing Von Gronau -- Secrets, spies, and mystery holes -- Survival versus sin -- The death-dealing sweetheart with the Jack Dempsey crouch -- "The gun-craziest man I ever met" -- Bust 'em George, the undocumented renegade general -- Clara Crosby comes of age -- Margaret, pappy's radical, scrappy, lethal engine of death -- The war on hope -- Blood and fire -- Reconnections and revolutions -- Part 3 Homeward bound -- Later legends -- Gunship summer -- Miss Priss strikes back -- The pinky and the lungs -- On the tail of Custer's ghost -- The vow of last resort -- Pappy's final battle -- The sweet Georgia peach -- War made animals of men -- Ward Six.
Includes bibliographical references (pages 499-512) and index.
Keywords: Gunn, Paul Irvin -- 1899-1957.; Gunn, Paul Irvin -- 1899-1957 -- Family; Philippine Airlines -- Officials and employees -- Biography; World War, 1939-1945 -- Aerial operations, American; Air pilots -- United States -- Biography; Aeronautics, Military -- Technological innovations -- History -- 20th century; Americans -- Philippines -- Biography; Prisoners of war -- Philippines -- Biography